Stress management in obesity during a thermal spa residential programme (ObesiStress): protocol for a randomised controlled trial study. Issue 12 (23rd December 2019) - Dutheil, Frédéric; Chaplais, Elodie; Vilmant, Audrey; Courteix, Daniel; Duche, Pascale; Abergel, Armand; Pfabigan, Daniela M; Han, Shihui; Mobdillon, Laurie; Vallet, Guillaume T; Mermillod, Martial; Boudet, Gil; et al.
Abstract : Introduction: Stress and obesity are two public health issues. The relationship between obesity and stress is biological through the actions of stress on the major hormones that regulate appetite (leptin and ghrelin). Many spa resorts in France specialise in the treatment of obesity, but no thermal spa currently proposes a specific programme to manage stress in obesity. The ObesiStress protocol has been designed to offer a new residential stress management programme. This thermal spa treatment of obesity implements stress management strategies as suggested by international recommendations. Methods and analysis: 140 overweight or obese participants with a Body Mass Index of >25 kg/m 2 and aged over 18 years will be recruited. Participants will be randomised into two groups: a control group of usual practice (restrictive diet, physical activity and thermal spa treatment) and an intervention group with stress management in addition to the usual practice. In the present protocol, parameters will be measured on five occasions (at inclusion, at the beginning of the spa (day 0), at the end of the spa (day 21), and at 6 and 12 months). The study will assess the participants' heart rate variability, cardiac remodelling and function, electrodermal activity, blood markers, anthropometric profile, body composition, psychology and quality of life via the use of questionnaires and bone parameters. Ethics and dissemination: The ObesiStress protocol complies with the ethics guidelines for Clinical Research and has been approved by the ethics committee (CPP Sud-Est VI, Clermont-Ferrand - ANSM: 2016-A01774-47). This study aimed to highlight the efficacy of a 21-day thermal spa residential programme of stress management in obesity through objective measurements of well-being and cardiovascular morbidity. Results will be disseminated during several research conferences and articles published in peer-reviewed journals. Trial registration number: NCT03578757 .